2013
DOI: 10.1002/jmri.24428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between high-resolution isotropic three-dimensional and high-resolution conventional two-dimensional FSE MR images of the wrist at 3 tesla: A pilot study

Abstract: With regard to clinical applications, 3D MRI of the wrist has almost equal potential to 2D MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…High‐resolution three‐dimensional (3D) structural MR imaging can accurately delineate complex or small structures of the body . However, it requires long acquisition times, thereby limiting its clinical use .…”
Section: Introductionmentioning
confidence: 99%
“…High‐resolution three‐dimensional (3D) structural MR imaging can accurately delineate complex or small structures of the body . However, it requires long acquisition times, thereby limiting its clinical use .…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have compared the diagnostic performances of 3D isotropic sequences and 2D sequences in the wrist joints, most of these used a gradient-recalled echo sequence 8,23 or FSE images with intermediate-weighted sequences. 8,21,22 We used 3D isotropic T 1 weighted FSE sequences in this study, and to our knowledge, it was the first such study on the wrist joint. This sequence uses flip angle sweep, short and non-volume selective refocusing pulse, and parallel imaging, which makes it possible to get shorter echo spacing and a better signal-tonoise ratio.…”
Section: Patient Data and Results Are Summarized Inmentioning
confidence: 99%
“…10,[18][19][20] However, the number of studies that have used 3D isotropic FSE techniques in the wrist joint is limited. 8,21,22 Additionally, although the D-MRA 3D isotropic FSE sequence provides high contrast and spatial resolution, only one study to date has reported the diagnostic performance of 3D isotropic FSE D-MRA for the wrist joint. 21 However, they used 3D isotropic proton-density FSE MRI instead of T 1 weighted FSE MRI and did not use the arthroscopic findings Full paper: Diagnostic performance of wrist magnetic resonance (MR) arthrography BJR as the gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…1 Increased slice thickness results in decreased scan time at the cost of increased image blur. Overall, decreasing ETL improves image blur.…”
Section: Techniquementioning
confidence: 99%